Provision of educational facilities for visually impaired learners at tertiary level in Pakistan: a review study - Malik, Shazia; Abdul Manaf, Umi Kalthom; Ahmad, Nor Aniza; Ismail, Maimunah (Zes Rokman Resources, 2018)
The primary purpose of the present study is to describe a detailed review of the capabilities of visually impaired learners at tertiary level from an emic view point. The information was collected from visually impaired learners, who were studying in three universities in Islamabad, Pakistan; Quaid-e-Azam University, International Islamic University, and National University of Modern Languages (NUML). The findings of the research reveal the main issues which were encountered by the visually impaired learners at tertiary level. Further, they explained their educational approaches which were used by their institutes to overcome their difficulties. Regardless their feelings of less importance, they were facing educational atmosphere unfriendly, but experiences and feelings of the visually impaired learners’ much emphasized on the opinions of approval by their friends which appeared quite important to them. To enable the visually impaired learners in strengthening their participation at tertiary level, the study prescribes the need to go past incorporation and uniformity models to guarantee the value and equality in universities. To transform this in a routine practice learning institutes have to play a substantial part.